Optimizing nano-solution coating method and ball milling method to achieve maximum non-linearity property for ZnO-based low-voltage varistor ceramics - Dorraj, Masoumeh (2014)
In ZnO based low voltage varistor ceramics, the microstructure development is depends on Bi2O3, TiO2 and Sb2O3 molar ratio. Thus, the selection of a composition with an appropriate molar ratio is completely important. In this study, the optimal levels of these dopants to achieve maximized nonlinear electrical property (alpha) were quantified by the response surface methodology (RSM) for the nano-solution coating (NSC) and ball milling (BM) methods. Secondly, the electrical and physical properties of optimized samples obtained by both methods were compared with each other. The central composite rotatable design consisting of three variables and alpha as a response, with 20 runs was used to conduct the experiments in each method. To obtain actual responses, the design was performed in laboratory by the NSC and BM methods. For both methods, the actual responses were fitted into a valid second order polynomial model. Then the analysis of variance (ANOVA) showed that the actual responses could be adequately fitted to quadratic polynomial model by several evidences. For the NSC method, these evidences included the high F-value (77.56), very low P-value (<0.0001), R-squared (0.986), adjusted R-squared (0.973) and predicted R-squared (0.950), while for the BM method consisted of the F-value (28.79), very low P-value (<0.0001), R-squared (0.963), adjusted R-squared (0.930) and predicted R-squared (0.780). The optimum values of additives were investigated by graphical and numerical optimization methods for both techniques. Based on these optimization methods, for NSC technique, the optimum values of Bi2O3, TiO2 and Sb2O3 in maximum alpha (14.52) were predicted 0.52, 0.50 and 0.30, respectively, while for BM technique in maximum alpha (9.47) were predicted 0.44, 0.40 and 0.29, respectively. Experiments were then carried out under the recommended conditions and resulting responses were compared to the predicted values. The results for both methods were quite close to the alpha values by the equation models. In conclusion, RSM has been successful for modeling and optimizing the additives such as Bi2O3, TiO2 and Sb2O3 of ZnO-based low voltage varistor ceramic to achieve maximized non-linearity properties in both methods. The highest value of alpha was obtained by NSC method (14.55) in compare the BM method (9.43). Moreover, the improvement in electrical properties of varistors made by NSC method could be explained by the homogeneous distribution of various dopant in the mixed powder and the more chemically uniform in structures.